Profesionalitas Aparatur PPPK: Peran Kinerja, Kompetensi, Motivasi, Dan Budaya Organisasi - Dedy Lasmono; Roy Haris Oktabian; Hamdan Hamdan; Efendi Sugianto; Panca Tuah Tuha (Public Service and Governance Journal, 2025)
This research was conducted with the aim of evaluating the extent of the professionalism of the apparatus within the Central Bangka Regency Government by examining how performance affects it, as well as evaluating the extent to which competence, motivation, and organizational culture contribute to the achievement of the performance of Government Employees with Employment Agreements (PPPK). By applying a quantitative approach and explanatory research design, data was obtained through a survey of 191 respondents, then analyzed using multiple linear regression methods and simple linear regression. The results of the analysis show that the three independent variables simultaneously or separately have a significant influence on employee performance, where organizational culture emerges as the most dominant factor. In addition, performance has been proven to make a positive and significant contribution to the formation of apparatus professionalism. These findings confirm that the level of professionalism cannot be separated from the work performance displayed, which is substantially determined by individual abilities, motivational drive, as well as the collective values that live in the organization's culture. Based on these results, the policy recommendations that can be drawn highlight the urgency to strengthen the organizational culture based on the core values of the State Civil Apparatus, encourage the development of competencies in accordance with the needs of the position, and reorganize the incentive system and performance evaluation to build a more professional and responsible bureaucracy.